2017
DOI: 10.3389/fcimb.2017.00254
|View full text |Cite
|
Sign up to set email alerts
|

Type VI Secretion Effectors: Methodologies and Biology

Abstract: The type VI secretion system (T6SS) is a nanomachine deployed by many Gram-negative bacteria as a weapon against eukaryotic hosts or prokaryotic competitors. It assembles into a bacteriophage tail-like structure that can transport effector proteins into the environment or target cells for competitive survival or pathogenesis. T6SS effectors have been identified by a variety of approaches, including knowledge/hypothesis-dependent and discovery-driven approaches. Here, we review and discuss the methods that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
108
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 106 publications
(225 reference statements)
0
108
0
2
Order By: Relevance
“…Here, using what is known from previously characterized T6SS‐dependent effectors, coupled with bioinformatic tools, we have identified additional putative T6SS‐dependent non‐TssI effectors and their cognate immunity proteins encoded by the B. cenocepacia genome. As T6SS‐dependent effector genes in other species are often located within close proximity to tssI genes (Lien & Lai, ), we used the predicted amino acid sequences of protein products encoded within close proximity to the ten intact tssI genes and one disrupted tssI gene (BCAL2503) present within the B. cenocepacia J2315 genome as queries in BLASTP searches to identify putative functional domains and homology to proteins belonging to established T6SS effector superfamilies (Appendix Figure A6). Twelve putative T6SS effectors were identified using this approach, with each of the tssI clusters in B. cenocepacia J2315 encoding at least one putative effector.…”
Section: Resultsmentioning
confidence: 99%
“…Here, using what is known from previously characterized T6SS‐dependent effectors, coupled with bioinformatic tools, we have identified additional putative T6SS‐dependent non‐TssI effectors and their cognate immunity proteins encoded by the B. cenocepacia genome. As T6SS‐dependent effector genes in other species are often located within close proximity to tssI genes (Lien & Lai, ), we used the predicted amino acid sequences of protein products encoded within close proximity to the ten intact tssI genes and one disrupted tssI gene (BCAL2503) present within the B. cenocepacia J2315 genome as queries in BLASTP searches to identify putative functional domains and homology to proteins belonging to established T6SS effector superfamilies (Appendix Figure A6). Twelve putative T6SS effectors were identified using this approach, with each of the tssI clusters in B. cenocepacia J2315 encoding at least one putative effector.…”
Section: Resultsmentioning
confidence: 99%
“…For example, an eCIS called Photorhabdus Virulence Cassettes (PVC) injects an effector causing actin condensation in insect hemocytes (Yang et al, 2006). In T6SS, a number of effectors are described that specifically target eukaryotic cells (Lien and Lai, 2017). The modes of action of these T6SS effectors include actin cross-linking in macrophages (Pukatzki et al, 2007), interaction with microtubules for invasion of epithelial cells (Sana et al, 2015), and disruption of the actin cytoskeleton of HeLa cells (Suarez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Contraction of the sheath enables the HCP-VgrG-PAAR protein complex to puncture the bacterial membrane and deliver various T6SS effectors into the extracellular environment or directly into the target bacterial cells 8,15,16 . The effectors can be encoded either as fused protein with the HCP/VgrG/PAAR proteins as an additional domain or they are non-covalently fused to HCP/VgrG/PAAR protein that are encoded as upstream ORF in the effector operon 12,15,1720 . Association with HCP/VgrG/PAAR proteins/domains is essential for translocation of effectors.…”
Section: Introductionmentioning
confidence: 99%
“…Association with HCP/VgrG/PAAR proteins/domains is essential for translocation of effectors. Recent studies have suggested that certain chaperone (DUF4123, DUF1795 and DUF2169) and co-chaperones are also required for T6SS mediated delivery of effectors 2023 . Till date, diverse kinds of proteins including phospholipases (Tli), amidases (Tae), glucosaminidase (Tge), nucleases (Rhs proteins), DNases (Tde), peptidases, pore-forming toxins etc.…”
Section: Introductionmentioning
confidence: 99%